ZNF146 accelerates lung adenocarcinoma progression through MDM2/p53 and PHGDH/ferroptosis - Junkan Zhu; Shencheng Ren; Yanjun Yi; Zhiyao Wu; Han Lin; Guangyao Shan; Xiaolong Huang; Binyang Pan; Zhengyang Hu; Qihai Sui; Cheng Zhan; Shuai Wang; et al. (Cell & Bioscience)
Abstract Background Lung adenocarcinoma (LUAD) remains a significant contributor to cancer incidence and mortality, with transcription factors playing pivotal roles in its progression and serving as potential therapeutic targets. Results Through an extensive analysis of expression data from over a thousand LUAD samples, we identified zinc finger protein 146 (ZNF146) as a transcription factor significantly overexpressed in LUAD, closely associated with poor patient outcomes. Functional studies using knockout and re-expression experiments in LUAD cell lines confirmed that ZNF146 robustly promotes cell proliferation. RNA-seq and ChIP-seq data integration further revealed two key downstream effectors of ZNF146: murine double minute 2 homolog (MDM2) and phosphoglycerate dehydrogenase (PHGDH). Our results demonstrated that ZNF146 accelerates LUAD progression via the MDM2/p53 pathway and PHGDH-mediated regulation of ferroptosis. Conclusions Our findings indicate that targeting ZNF146 could be an effective strategy in treating LUAD, supported by evidence from adeno-associated virus-mediated inhibition of ZNF146, which suppressed tumor growth in patient-derived organoids and xenograft models.